Outcomes of treatment for right atrial isomerism with functional single ventricle and extracardiac total anomalous pulmonary venous connection beyond neonatal period: Delayed surgical treatment, improving outcomes - Chen, Weidan; Lu, Ye; Ma, Li; Yang, Shengchun; Zou, Minghui; Li, Wenlei; Chen, Xinxin (Frontiers in Cardiovascular Medicine, 2022)
Objective Total anomalous pulmonary venous connection (TAPVC) is frequently associated with right atrial isomerism (RAI), which is commonly complicated with an unbalanced atrioventricular canal with contralateral hypoplasia, complex systemic and pulmonary venous anatomy, and conotruncal abnormalities, resulting in increased risk of mortality. This study aimed to review the outcomes of delayed surgical treatment for patients with RAI complicated with functional single ventricle (FSV) and TAPVC at a single center. Methods In this retrospective study, we reviewed the medical records of 24 consecutive patients with RAI complicated with FSV and TAPVC who underwent initial surgical palliation after 5-month old between September 2008 and June 2019. Demographic data, concomitant anomalies, age at initial palliation, and surgical interventions were extracted and analyzed using the Cox proportional hazard model to assess risk factors for mortality and the Kaplan-Meier method to assess survival. Results The in-hospital mortality was 12.5% (three out of 24). The causes of death were pulmonary arterial hypertension and low cardiac output syndrome. Average follow-up was 65.2 ± 40.3 months (7–137 months). Another 4 patients died during the follow-up due to low cardiac output syndrome, protein-losing enteropathy and pulmonary arterial hypertension, respectively. Kaplan-Meier estimated survival at 1 and 5 years were 83.1 and 69.4%, respectively. Fontan completion was 45.8% (11/24). The mortality for patients with pulmonary venous obstruction (PVO) was 66.7% (4/6). Cox multivariate regression analysis indicated that preoperative PVO was the only risk factor for mortality (p = 0.032; hazard ratio, 10.000; CI 1.222–81.811). Conclusion Outcomes of delayed surgical treatment for patients with RAI complicated with FSV and TAPVC have improved significantly. The survival and Fontan completion were higher. However, preoperative PVO was still the risk factor for mortality.